Measurements of differential cross sections of top quark pair production in association with jets in pp collisions at √s=13 TeV using the ATLAS detector - Palazzo, Serena; Carbone, Vincenzo; La Rotonda, Laura; Faucci Giannelli, Michele (My University, 2018)
In this thesis the measurements of differential cross sections of top quark pair production in association with jets are presented. Data collected by the ATLAS experiment at the LHC during the 2015 corresponding to an integrated luminosity of 3.2 fb􀀀1 were used. The top quark pair events are selected in the lepton (electron or muon) + jets channel. Several variables are selected because are sensitive to additional jets: the top quark tranverse momentum, the transverse momentum of the top quark anti-top quark system and of the outof- plane transverse momentum. The measured cross sections are compared to several theoretical Monte Carlo predictions and allow detailed studies of the top quark production. In this thesis the work on the new MicroMegas tracking chambers which will be installed in the Muon Spectrometer during the Phase-1 Upgrade of the ATLAS detector, is also presented. The performances of the first chamber prototype built by the INFN Italian collaboration and tested on beam at CERN on June 2016 are reported.
Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXX
Keywords: Particles (Nuclear physics)Quantum field theory; Quantum field theory